(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2024)
Hypertension refers to a condition where the systemic artery blood pressure exceeds normal levels, necessitating increased cardiac effort to counteract the elevated pressure and ensure adequate blood flow to tissues. The heightened systemic arterial pressure places stress on the heart and other arteries, contributing to the development of hypertension. In our cross-sectional observational study, we employed questionnaires to gather data from volunteers over a three-month period. The inclusion and exclusion criteria were carefully applied to ensure the relevance of the collected data. Our study included 120 individuals from the selected region, aiming to assess blood pressure monitoring. The study revealed a dominance of males, constituting 51.67% of the total participants, while women accounted for 48.33%. The age distribution showed that 46.67% of the volunteers fell within the 31 to 40 age group. Our findings indicated that age, gender, and occupation significantly influenced blood pressure monitoring. Upon analysis, we observed a statistically significant improvement in volunteers’ knowledge, attitudes, and practices regarding hypertension following counseling. This suggests the potential efficacy of intervention strategies in enhancing awareness and management of hypertension among the studied population.